An integrated scheduling method for AGV routing in automated container terminals - Yang, Y.; Zhong, M.; Dessouky, Y.; Postolache, O. (Computers and Industrial Engineering, 2018)
The simultaneous scheduling of quay cranes (QCs), automated guided vehicles (AGVs), and yard cranes (YCs) in automated container terminals (ACTs) has been a critical problem. This paper proposes an integrated scheduling for handling equipment coordination and AGV routing. With the goal of minimising makespan, we set up a bi-level programming model. To solve the model, we investigate and compare the rolling horizon procedure (RHP) and Congestion Prevention Rule-based Bi-level Genetic Algorithm (CPR-BGA). It is shown that the CPR-BGA algorithm is highly effective for the integrated scheduling in ACTs. We conclude that the CPR-BGA is effective.